In the following simplification why doesn't Mathematica get a zero when asked to compute "Y-Z" eventually?
a = 1 - 4 A Q^2;
b = (-972 + 648) A Q^2 + 54;
c = 9 - 36 A Q^2;
Y = 12 Q/(
Sqrt[A] (
2 - (3 2^(1/3) a )/(Sqrt[b^2 - 4 c^3] + b )^(1/3) - (
Sqrt[b^2 - 4 c^3] + b )^(1/3)/( 3 2^(1/3) ) ) );
Z = (4/A) + (3 2^(1/3) a )/(A (Sqrt[b^2 - 4 c^3] + b )^(1/3) ) + (
Sqrt[b^2 - 4 c^3] + b )^(1/3)/( 3 2^(1/3) A);
Q = Sqrt [ 3/(16 A)];
Y - Z // FullSimplify
(-9 + 4 Sqrt[3] Sqrt[1/A] Sqrt[A])/(2 A)
One can do the above calculation by hand and one would see that for the specific chosen value of $Q = \sqrt{3/16 A}$ one would get $Y = Z = \frac{3}{A}$. Why doesn't Mathematica see this?
- And is there a way to get Mathematica to detect if there are other values of $Q$ where $Y = Z$? (..I found this one value special value of $Q$ by just staring at the equation for sometime...)
Rewriting the functions again.
$Y = \frac{12Q}{\sqrt{A}\sqrt{ 2 - \frac{3 (2^{1/3})a }{(\sqrt{b^2 - 4 c^3 } + b )^{1/3} } - \frac{(\sqrt{b^2 - 4 c^3 } + b )^{1/3} }{3 (2^{1/3})} } }$
$Z = \frac{1}{A} \left (4 + \frac{(\sqrt{b^2 - 4 c^3 } + b )^{1/3} }{3 (2^{1/3})} + \frac{3 (2^{1/3})a }{(\sqrt{b^2 - 4 c^3 } + b )^{1/3} }\right ) $
at the chosen values of $Q = \sqrt{\frac{3}{16A} }$ one has $a = \frac{1}{4}$ and $b = - \frac{27}{4}$ and $b^2 - 4 c^3 = 0$. Also whenever I encounter $b^{1/3}$ I am writing that as $-3 \times 2^{-2/3}$. Substituting these into the above one gets $Y = Z = \frac{3}{A}$
$Assumptions = {A > 0}; Y - Z // FullSimplify
but it seems there is a mistake somewhere. $\endgroup$